Pengaruh Mobilisasi Dini terhadap Perubahan Tingkat Nyeri Klien Post Operasi Apendektomi di Rumah Sakit Baladhika Husada Kabupaten Jember (The Effect of Early Mobilization on The Change of Pain Level in Clients with Post Appendectomy Operation at Mawar S - Caecilia Yudistika Pristahayuningtyas; Murtaqib Murtaqib; Siswoyo Siswoyo (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Appendectomy is a procedure that can cause pain. The clients with post appendictomy operation need the maximal treatment to return the body function quckly. One of non pharmacological therapy that can be used to decrease the pain is early mobilization. Early mobilization is useful to distract clients from the pain. The objective of this research was to analyze the effect of early mobilization on the change of pain level in clients with post appendectomy operation at Mawar Surgical Room of Baladhika Husada Hospital Jember Regency. Independent variable of this research was early mobilization and dependent variable was the change of pain level. This research used pre experimental: one group pretest posttest design. The sampling collection technique used was consecutive sampling involving 8 individuals. Data analysis used t-dependent testing with the significance level of 95% (α=0,05). Data analysis regarding dependent t-test showed that there was a significant difference between pretest and posttest after early mobilization (p=0,000). The conclusion of this research suggested that there is an effect of early mobilization on the change of pain level. The early mobilization is expected to be applied as one of methods in providing nursing care to clients with post appendectomy operation. Keywords: early mobilization, appendectomy, pain